Application of Antigen Cross-Presentation Research into Patient Care - Marianne Boes (Frontiers Research Topics, 2017)
The activation of adaptive immune responses requires the processing and presentation of protein antigens to lymphocytes. Especially dendritic cells are effective at display of antigen-derived peptides in the form of immunogenic peptide/MHC complexes to CD4 and CD8-positive T cells, and can stimulate even naive T cells to clonally expand. During the last 40 years, mechanisms that facilitate antigen processing and presentation were clarified, mostly from work in cell lines and mouse models. From mouse-based work, it is now clear that dendritic cells represent a collection of specialized cell subsets that are particularly well endowed to stimulate antigen transport to distinct tissue locations, to transfer antigens between cellular subsets or to trigger T cell responses. Dendritic cell subsets hold great promise for therapeutic application, for example as dendritic cell-based vaccines to bolster immune responses against viruses or malignant growths. Hurdles remain that preclude the efficient application of high quality pre-clinical research into standardized patient care. In this research topic, efforts in dendritic cell research and dendritic cell-based vaccines are discussed, from both pre-clinical and application points of view.